Liability of construction participants for delays - Mitkus, Sigitas; Sekonaitė, Aurelija (Business, Management and Economics Engineering, 2011)
Date of completion is usually set forth in construction contract agreements as one of the most important provisions. Also, it is the provision, which is often violated and the violation results in a dispute between the parties to the agreement. Analysis of research literature has revealed that most authors analyse and identify causes of delays in construction as well as recommend delay analysis methods omitting or underemphasising the liability of the parties to construction contract agreements for violation of construction completion date. One more problem in this area is the difficulty in applying practices of different countries in a specific country due to differences in legislative frameworks. Cases described in research literature are often idealised, while realistic construction projects frequently possess various specific features. This article aims at identifying problems faced when assessing the liability of construction participants for violation of completion date and suggesting ways to handle the problem.